A música sacra litúrgica nas igrejas batistas e presbiterianas históricas em Montes Claros: entre a tradição e a inovação - Silva, Waldir Pereira da (2016)
The present work investigates aspects related to the use of sacred music in the liturgy of the cults of historic Baptist and Presbyterian churches in the city of Montes Claros - MG. The specific objective is to check the current reality of musical activities in these churches, identifying the conceptions and practices that underpin their cultic musical activities. This is an emerging theme that needs of more systematic studies that allow understand the musical activities in the referred churches, from the action of pastors, and "praise ministries" and where are founded their cultic musical practices. It is relevant cast a critical eye on the reality of musical activities of these churches, and that allows knowing the reality of other historic churches in the field of cultic music. It is understood that this proposed of study suits the prospects of scientific production at present and covers problems and specific situations of socio-cultural and political contexts of the studied churches. The working hypothesis was: the process of musical Pentecostalization disliturgied the sacred music used in cults of the historical Protestant churches by influence of gospel musical market. The research universe consists of two historic Baptist churches and two Presbyterian churches, and the research was divided into two phases: on the first, it was held an initial survey of how many Baptist and Presbyterian historic churches exist in Montes Claros, and made up the choose of four of them to carry out the fieldwork research. In the second phase, priority was given to the particular reality of each church selected, with respect to their musical activities. The work was developed from bibliographical research, documentary research, semi-structured interviews, questionnaires, participant observation, photographic records and in audio and video of the cultic musical activities in each one of the four selected churches. The obtained results point to a supremacy of using of the called gospel music in relation to official hymnody of each denomination, the print media being replaced by electronic media and significant changes in cultic liturgy of each church